El derecho a la autodeterminación de las personas y su connotación histórica constitucional en el Estado democrático ecuatoriano. - Cauja Tierra, Alex Jofre (2023)
This research paper analyzes the right to self-determination; it is considered an intrinsic right of a particular group of people, whose purpose is to determine the necessary guarantee to provide the freedom of autonomy as well as identity; In addition, it is examined whether this right is faithfully complied with by the State, for which the corresponding constitutional norms that guarantee the right to self-determination and the effectiveness in the applicability from the point of view of the indigenous communities and peoples are exposed. With the intangible objective of achieving this analysis, it starts with the study of the historical evolution of the right to self-determination within our country, to then project it externally to analyze the protection of this right from an international approach through a study of comparative law in countries such as Bolivia, Venezuela, and Peru; to expose the possible causes that may transgress this right, in addition to the legal effects of its non-observance, finally, to analyze a case inherent to the right to self-determination. In this way, through this research, it can be concluded whether or not this right is violated in our country, especially when dealing with indigenous, Montubios and afro Ecuadorian peoples and nationalities, as well as its historical constitutional connotation within a democratic state like ours.